Prediction of EGFR Mutation Status in Non–Small Cell Lung Cancer Based on Ensemble Learning - Feng, Youdan; Song, Fan; Zhang, Peng; Fan, Guangda; Zhang, Tianyi; Zhao, Xiangyu; Ma, Chenbin; Sun, Yangyang; Song, Xiao; Pu, Huangsheng; Liu, Fei; Zhang, Guanglei (Frontiers in Pharmacology, 2022)
Objectives: To identify whether ensemble learning can improve the performance of epidermal growth factor receptor (EGFR) mutation status predicting model. Methods: We retrospectively collected 168 patients with non-small cell lung cancer (NSCLC), who underwent both CT examination and EGFR test. Using the radiomics features extracted from the CT images, an ensemble model was established with four individual classifiers: logistic regression (LR), support vector machine (SVM), random forest (RF) and extreme gradient boosting (XGBoost). The synthetic minority over-sampling technique (SMOTE) was also used to decrease the influence of data imbalance. The performances of the predictive model were evaluated using the area under the curve (AUC). Results: Based on the 26 radiomics features after feature selection, SVM performed best (AUCs of 0.8634 and 0.7885 on the training and test sets) among four individual classifiers. The ensemble model of RF, XGBoost and LR achieved the best performance (AUCs of 0.8465 and 0.8654 on the training and test sets). Conclusions: Ensemble learning can improve the model performance on predicting the EGFR mutation status of patients with NSCLC, showing potential value in clinical practice.